Therapist's effect on children's therapeutic alliance : A naturalistic study - Casari, Leandro Martín (2023)
Fil: Casari, Leandro Martín. Pontificia Universidad Católica Argentina. Facultad de Humanidades y Ciencias Económicas; Argentina